2019
DOI: 10.12669/pjms.35.2.638
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of energy drinks among Turkish University students and its health hazards

Abstract: Objective: To determine the awareness, consumption patterns of energy drinks (ED) and health hazards among students at a Turkish University. Methods: This cross-sectional descriptive study was conducted by questionnaire method between in 2017 among Erciyes University students. Total 1257 students from the Faculties of Medicine, Communication and Physical Education and Sports College participated in the study. Pearson chi-square test, binary logistic regressions were used for statistical analysis. p <0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 21 publications
7
17
3
1
Order By: Relevance
“…The present study found the prevalence of ED consumption among participants to be 47.4 per cent. It is similar with the findings of other studies carried out in Saudi Arabia, where 46 per cent of respondents consumed ED (Faris, 2014), Nigeria, where 44.2 per cent of the adolescents consumed ED (Sholeye et al, 2018), Norway, where 52.3 per cent of adolescents were ED consumers (Degirmenci et al, 2018), and among Turkish university students where 52.5 per cent of students consumed ED (Borlu et al, 2019). However, our findings is much higher than some studies conducted among Turkish university students, where 22.5 per cent students consumed ED (Bulut et al, 2014), in Canada, where 15.6 per cent of youth and young adults (Wiggers et al, 2017), in Saudi Arabia, where 19.5 per cent of university students (Alabbad et al, 2019) and in Zambia, where 27.4 per cent of university students (Mwape and NFS 50,1…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found the prevalence of ED consumption among participants to be 47.4 per cent. It is similar with the findings of other studies carried out in Saudi Arabia, where 46 per cent of respondents consumed ED (Faris, 2014), Nigeria, where 44.2 per cent of the adolescents consumed ED (Sholeye et al, 2018), Norway, where 52.3 per cent of adolescents were ED consumers (Degirmenci et al, 2018), and among Turkish university students where 52.5 per cent of students consumed ED (Borlu et al, 2019). However, our findings is much higher than some studies conducted among Turkish university students, where 22.5 per cent students consumed ED (Bulut et al, 2014), in Canada, where 15.6 per cent of youth and young adults (Wiggers et al, 2017), in Saudi Arabia, where 19.5 per cent of university students (Alabbad et al, 2019) and in Zambia, where 27.4 per cent of university students (Mwape and NFS 50,1…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the side effects that have been found among the ever ED user were thirst, headache, irritability, insomnia/sleeplessness, anxiety, restlessness and vertigo/dizziness. The most common side effects cited by the previous studies among the students in America, Turkey and Pakistan were unsteadiness, falls, headache, palpitations, sleeplessness, thirst, stress, weight gain and vertigo (Malinauskas et al, 2007;Aslam et al, 2013;Bulut et al, 2014;Hammond et al, 2018;Borlu et al, 2019;Mwape and Mulenga, 2019). Therefore, the consumers who take ED must bear in mind about the heterogenous adverse consequences of ED consumption, including death.…”
Section: Consumption Of Energy Drinkmentioning
confidence: 99%
“…The most common side effects reported by ED users in our study were anxiety, thirst, restlessness, insomnia/sleeplessness, irritability, headache and vertigo/dizziness. Similar side effects were observed among ED consumers in the study conducted in America, Turkey, Pakistan and other countries [3,8,15,17,19,22,23].…”
Section: Discussionsupporting
confidence: 82%
“…The common reasons for consuming ED reported by the participants were its taste, feeling more energetic, to boost performance during exercise and to increase concentration while studying. Other similar studies recorded similar reasons [3,4,8,15,17,19,22,24,25].…”
Section: Discussionsupporting
confidence: 63%
“…A Turkish study found that energy drink use among students of the arts and sports were the highest, whereas in the findings of the current study, students of economics were among the highest; however, students of economics were not included in the Turkish study [27]. In other studies it was noticed that energy drinks consumption was most common among Physical Education and Sport students [28,29]. The presented study did not include students from this faculty, although it may be assumed that the most physically active students among all the included universities were from the faculty of economics.…”
Section: Discussioncontrasting
confidence: 75%